Hematological disorders as a complication of COVID-19 - Yu.I. Markov; I.A. Markova; N.V. Goriainova; B.M. Kuiavovych (Медицина неотложных состояний, 2023)
Background. Coronavirus disease (COVID-19) can affect the blood and hemostasis systems and lead to complications that require intensive care. The aim is to detect such common complications by studying literary sources and clinical experience. Materials and methods. The search for relevant literature was conducted in PubMed, and in the other databases such as Science Direct, Google Scholar, Scopus and Web of Science. The literature search was done using the keywords “COVID-19”, “SARS-CoV-2” in combination with “coagulation dysfunction”, “coagulopathy”, “hematological manifestations”, “hematological parameters”, “deep vein thrombosis”, “pulmonary embolism”, “arterial thrombosis”, “D-dimer”, “fibrinogen”, “lymphopenia”, “thrombocytopenia”. Results. COVID-19-associated coagulopathy is characterized by high levels of D-dimer and fibrin degradation products in blood plasma, changes in prothrombin time, activated partial thromboplastin time, fibrinogen, and platelet count. Endothelial dysfunction caused by coronavirus leads to an increased risk of thrombotic complications, both in venous and arterial systems, additionally to the existing higher risk of thrombosis in the intensive care unit. The venous thromboembolism frequency among unvaccinated hospitalized patients and during ultrasound screening is significantly higher. Coronavirus disease can lead to arterial thrombosis in areas such as the aorta, kidneys, cerebral and peripheral arteries. COVID-19 can cause enhanced-fibrinolytic-type disseminated intravascular coagulation or limited thrombotic microangiopathy. According to research, patients with severe COVID-19 usually had leukocytosis, lymphopenia, and an elevated neutrophil-to-lymphocyte ratio. Thrombocytopenia is observed not only during the acute coronavirus disease, but also in the post-COVID-19 period. Both thrombosis and bleeding can occur in patients undergoing extracorporeal membrane oxygenation. Conclusions. A high level of D-dimer, a prolongation of prothrombin time, an increase or a quick decrease in fibrinogen level, lymphopenia, neutrophilia, and an increase in the neutrophil-to-lymphocyte ratio are considered prognostic factors for the severity of coronavirus disease. Deep vein thrombosis and pulmonary embolism are the most common thrombotic events in patients with COVID-19. Arterial thrombosis occurs more often in the cerebral arteries and arteries of the extremities.